Building a Faithful Environment: A Study of Urban Farming in Setia Jaya Tulungagung Housing Complex - A Zahid, A Zahid (Indonesian Journal of Social Responsibility Review (IJSRR), 2025)
The purpose of this study was to explore the potential of urban farming as a way to create a religious environment in the Setia Jaya Tulungagung neighbourhood. Urban farming that utilizes limited land is known as urban farming. It serves as a source of food, helps education, and improves residents’ quality of life. For this study, residents were interviewed and observed using qualitative methods. The results showed that urban farming in Setia Jaya Tulungagung can strengthen religious values ​​through community-based activities that emphasize togetherness, environmental awareness, and wise use of resources. According to spiritual teachings, communal gardening activities teach residents to be more grateful and increase a sense of sharing. As a result, urban farming benefits food security and improves the community’s social ties and spiritual life.